1989
DOI: 10.1007/bf00190210
|View full text |Cite
|
Sign up to set email alerts
|

Learning and discrimination of coloured papers in the walking blowfly, Lucilia cuprina

Abstract: A new training and testing paradigm for walking sheep blowflies, Lucilia cuprina, is described. A fly is trained by presenting it with a droplet of sugar solution on a patch of coloured paper. After having consumed the sugar droplet, the fly starts a systematic search. While searching, it is confronted with an array of colour marks consisting of four colours displayed on the test cardboard (Fig. 1). Colours used for training and test include blue, green, yellow, orange, red, white and black. Before training, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
3

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 15 publications
2
43
0
3
Order By: Relevance
“…Further physiological data are necessary to put these conjectures to the test. We may note that the central photoreceptors of flies mediate colour vision in blowflies (Fukushi 1989;Troje 1993). A specific colourful role has also been inferred for the central photoreceptors of dolichopodids, which have two types of spectrally conjugated corneal reflectors organized in extremely regular, interlaced patterns (Bernard 1971).…”
Section: The Bright Colours Of Tabanid Eyes May Reflect a Filter Funcmentioning
confidence: 81%
See 1 more Smart Citation
“…Further physiological data are necessary to put these conjectures to the test. We may note that the central photoreceptors of flies mediate colour vision in blowflies (Fukushi 1989;Troje 1993). A specific colourful role has also been inferred for the central photoreceptors of dolichopodids, which have two types of spectrally conjugated corneal reflectors organized in extremely regular, interlaced patterns (Bernard 1971).…”
Section: The Bright Colours Of Tabanid Eyes May Reflect a Filter Funcmentioning
confidence: 81%
“…Convincing evidence for colour vision in other insects has been obtained only recently. The photoreceptor cells mediating colour vision in the blowfly Lucilia, the central photoreceptors R7 and R8 (Fukushi 1989;Troje 1993), exist in two pairs with different visual pigments. The two pairs are randomly distributed in the retina, i.e.…”
Section: Colours Seen By Insect Eyesmentioning
confidence: 99%
“…HALL (1995) also observed the preferential attraction of L. cuprina to the color yellow, and observed similar behavior by phytophagous species that are preferably attracted to this color. On the other hand, FUKUSHI (1989) observed that the more attractive trap colors for this species were blue and yellow, with red and black being the least attractive colors. WALL & SMITH (1996) studied the color discrimination by the sheep blowfly Lucilia sericata (Meigen, 1826).…”
Section: Speciesmentioning
confidence: 81%
“…It is generally agreed that R7 and R8 receptors feed into color-coding mechanisms; however, the exact contribution of the two subtypes of R7 and R8 receptors belonging to two ommatidial types is still unknown. Experiments by Troje (1993) and Fukushi (1985Fukushi ( , 1989 with Lucilia indicate that both subtypes may be involved. Since in our experiments the UV range was not used, the R8 receptors were the most strongly excited ones (Fig.…”
Section: Learning and Memory 631mentioning
confidence: 97%